SAR and Molecular Docking Studies for the development of new Tyrosinase inhibitors (Research, Society and Development, 2022)
Tyrosinase is an enzyme that participates in melanin biosynthesis. Therefore, it is considered a very important enzyme for some physiological processes, in addition, it is involved from the browning process of some fruits to Parkinson's neurodegeneration. Thus, kojic acid is an important metabolite that has the property of inhibiting the tyrosinase enzyme in relation to the production of melanin. Thus, kojic acid is widely used in medicine, thus characterizing itself as important for certain types of treatments. Therefore, in this project we use molecular modeling approaches to analyze kojic acid derivatives, a molecular target against the tyrosinase enzyme, initially the optimization and parameterization were performed using the semi-empirical PM3 method. Subsequently, the methods were optimized by the TFD method, then using the MVD computer program, the energy calculations for the molecules were performed. Taking as a guide for the definition of structural parameters the Tropolone structure for computational analyzes targeting kojic acid and its derivatives. Thus, the results obtained in the simulations reached satisfaction. Based on the energy values obtained through the analysis, derivatives 2,3,8 and 9 are suggested as potential candidate molecules for tyrosine inhibitors.